HIGH DOSES OF KETAMINE INFLICT MYOCARDIAL INJURY AND CAUSE CHANGES IN THE RELATIVE BODY WEIGHT TO HEART OF ADULT ALBINO WISTAR RATS - ANYIOM, ODEY PAUL; JULIUS, ANIAH; RAYMOND U, OKOLO; ANDREW DONATUS, ABUE; GBENGA, EWEOYA; UGBAKA, AJANG CLETUS; EMMANUEL, ODOM (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Ketamine is widely used as an anesthetic agent in surgery and emergency medicine. It is also used for procedural sedation, treatment of depression, pain management, and sometimes as a recreational drug. These uses, however, have recommended doses to prevent myocardial injury. This study, therefore, was designed to investigate the level of injury on the myocardium following the administration of high doses of ketamine and to determine the relative body weight to heart weight of the experimental animals. Method: A total of 12 male albino Wistar rats were used and grouped into four including the control group. They were weighed daily and administered 100 mg, 150 mg, and 200 mg/kg/body weight of ketamine intraperitoneally for 2 weeks and weighed again. Experiment was terminated after 14 days and animals were sacrificed and the heart harvested for analysis. Results: Ketamine caused a significant myocardial injury with increase in the doses in different groups by causing inflammation, hypertrophy, vacuolar degenerative changes, atrophy, and extensive hemorrhage around the myocytes. Weight differentiation was noticed in all experimental groups with heart weight contributing to the total body weight by 1.63%, 1.7%, and 1.2% for the 100 mg, 150 mg, and 200 mg/kg/body weight of ketamine groups, respectively. Conclusion: Higher doses of ketamine cause significant myocardial injury as well as differential changes in body weight and heart weight in experimental animals.